Effect of explants and auxins concentration on callus induction on peach (Prunus persica (L.) Batsch) micropropagation - Nazar Al Ghasheem (Zien Journals, 2022)
Micropropagation or plant tissue culture technique is one of the most appropriate methods for plant material multiplication in order to obtain healthy and disease free planting material in mass quantity and fast time. The amis of this study the impacts of explants and auxins on callus induction on peach micropropagation. Redhaven genotype from the Field of Faculty of Horticulture, University of Agronomic Sciences and Veterinary Medicine of Bucharest, Romania were tested. Two explants (shoots tips and nodes, 1cm length) were cultured on MS (Murashige and Skoog, 1962) basal medium plus vitamins supplemented with 30g/l sucrose, 7g/l agar and 500mg/l activated charcoal. Two auxins: Indole-3-butyric acid (IBA) in four concentrations: 0,1,3 and 5mg/l respectively and 1-Naphthaleneacetic acid (NAA) in four concentrations: 0,1,3 and 5mg/l respectively were used as plants hormones for callus induction. The growth chamber for the in vitro cultures had 22±2°C temperature and 70 - 80% relative humidity, with a photoperiod of 16h day light and 8h dark. The days of callus inductions; percentage of callus induction; rate of callus growth; fresh weight of callus and morphology of callus inducted were studied. The results showed a significant correlation between explants with the concentration of auxins on callus induction. The nodes explants and 5.00 mg/l NAA concentration gave the highest values in the recorded traits.
Keywords: auxins; callus induction; Indole-3-butyric acid; Redhaven